Non aqueous titrations: Potentiometric titration of some primary amines - Kocaoba, Sevgi; Aydogan, Feray; Afsar, Huseyin (FREUND PUBLISHING HOUSE LTD, 2008)
Potentiometric titrations of some primary amines; I-aminobutane, Iaminopropane and 3-amino-l-phenylbutane were carried out with hydrochloric acid in toluene solvent. The same titrations were done with hydrochloric acid in methanol solvent to show the effect of amphiprotic solvent in the titrations with hydrochloric acid. For each weak base, an Sshaped potentiometric titration curve was obtained. As a result, toluene, which is an aprotic inert solvent, is a suitable solvent for titrating some of the weak bases potentiornetrically.
Keywords: non-aqueous titrations; toluen; hydrochloric acid; aminobutane; 1-amino propane; 3-amino-1-phenylbutane; NONAQUEOUS MEDIA; TETRABUTYLAMMONIUM HYDROXIDE; NITROBENZENE SOLVENT; ACIDS; ACETONITRILE; Chemistry